Program Dokter Kecil Di UKS SD Negeri 3 Wonorejo Lawang - Wulandari, Mayang; Prihatonoa, Amal; Mahadinia, Chantika (Journal of Health Innovation and Community Services, 2025)
Abstract : Primary schools are vital ecosystems for children’s growth and development, yet the risks of accidents and illness are unavoidable; therefore, the School Health Unit (UKS) and the Young Doctor program (Dokter Kecil) play a pivotal role. This community‐service initiative aimed to optimize the UKS function at SDN 3 Wonorejo Lawang—which had been suboptimal due to a damaged room—and to strengthen students’ first-aid knowledge and skills. The intervention employed a participatory approach comprising UKS room renovation, provision of basic health facilities, and Young Doctor training; the evaluation design used a one-group pretest–posttest (quasi-experimental) on 10 students (n=10). Outcomes included school readiness via a checklist-based facility audit (availability, fitness for use, and utilization), first-aid knowledge via a 20-item questionnaire, and first-aid skills via a performance checklist (bandaging, simple immobilization, minor wound management); analyses used descriptive statistics and the Wilcoxon test (α=0.05). Results showed the UKS returned to optimal function with organized service flow and essential equipment available, alongside a significant improvement in participants’ first-aid knowledge and skills. We conclude that combining UKS facility improvements with student capacity building through the Young Doctor program effectively enhances school health service quality and emergency preparedness and is suitable for replication with a periodic monitoring–evaluation cycle to ensure sustainability.